Contrasting aerosol refractive index and hygroscopicity in the inflow and outflow of deep convective storms: Analysis of airborne data from DC3. Issue 8 (30th April 2017) - Sorooshian, Armin; Shingler, T.; Crosbie, E.; Barth, M. C.; Homeyer, C. R.; Campuzano‐Jost, P.; Day, D. A.; Jimenez, J. L.; Thornhill, K. L.; Ziemba, L. D.; Blake, D. R.; Fried, A.
Abstract: We examine three case studies during the Deep Convective Clouds and Chemistry (DC3) field experiment when storm inflow and outflow air were sampled for aerosol subsaturated hygroscopicity and the real part of refractive index ( n ) with a Differential Aerosol Sizing and Hygroscopicity Probe (DASH‐SP) on the NASA DC‐8. Relative to inflow aerosol particles, outflow particles were more hygroscopic (by 0.03 based on the estimated κ parameter) in one of the three storms examined. Two of three "control" flights with no storm convection reveal higher κ values, albeit by only 0.02, at high altitude (> 8 km) versus < 4 km. Entrainment modeling shows that measured κ values in the outflow of the three storm flights are higher than predicted values (by 0.03–0.11) based on knowledge of κ values from the inflow and clear air adjacent to the storms. This suggests that other process(es) contributed to hygroscopicity enhancements such as secondary aerosol formation via aqueous‐phase chemistry. Values of n were higher in the outflow of two of the three storm flights, reaching as high as 1.54. More statistically significant differences were observed in control flights (no storms) where n decreased from 1.50–1.52 (< 4 km) to 1.49–1.50 (> 8 km). Chemical data show that enhanced hygroscopicity was coincident with lower organic mass fractions, higher sulfate mass fractions, and higher O:C ratios of organic aerosol. Refractive index did not correlate as well with available chemical data. Deep convection is shown to alter aerosol radiative properties, which has implications for aerosol effects on climate. Key Points: Mean kappa values measured in outflows exceed those predicted by an altitude‐dependent entrainment model Refractive index is lower aloft (> 8 km versus < 4 km) in nonstorm conditions with high statistical significance, unlike on storm days with inflow and outflow data Enhanced hygroscopicity coincides with lower organic mass fraction, higher sulfate mass fraction, and higher O:C ratios of organic aerosol